A cross-sectional observational study about media and infection control practices: are photographic portrayals of healthcare workers setting a bad example?. Issue 1 (December 2015) - Spierings, E.; Spierings, P.; Nabuurs-Franssen, M.; Hopman, J.; Perencevich, E.; Voss, A.
Abstract Background Attempts to increase compliance with infection control practices are complex and are - in part - based on attempts to change behaviour. In particular, the behaviour of significant peers (role models) has been shown to be a strong motivator. While role models within the working environment are obviously the most important, some experts suggest that media and public display cannot be ignored. The aim of this present study was to examine the display of technique recommended by current infection control guidelines including the "bare below the elbow" principle, which is considered a basic requirement for good infection control in many countries, in sets of professional stock photos. Findings From 20 random photo-stock websites we selected pictures with search terms "doctor and patient" and "nurse and patient". In all selected photos a doctor or nurse and a patient were presented, healthcare workers (HCWs) were wearing white coats or uniforms, and their arms were visible. Each photo was evaluated with regard to: closure of white coat, sleeve length, personal clothing covered, hairstyle and presence of a wristwatch, bracelet and/or ring. Overall, 1600 photos were evaluated. The most common mistakes were with regard to HCWs' white coats/uniforms. Eighty-nine percent of the photos containing doctor's images were considered incorrect while 28 % of nurse-containing photos were incorrect. Conclusions The results seem to reflect the real world with only 40 % displaying correct behaviour with doctors being worse than nurses. It seems that the stereotypical image of a doctor does not agree with the current infection control guidelines. If we aim for higher compliance rates of HCWs, we need to change the social image of doctors and improve production, selection and display of stock photo images.